Polscy pisarze w ruchu muzealnym na progu II Rzeczypospolitej - Kielak, Dorota (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
This article reflects on the participation of Polish writers in the museum movement during World War I and the period when the borders of the Second Polish Republic were being formed. It highlights the institutional activities of these writers supporting the transformation and creation of new museums. The focus is on their journalistic activity, i.e. discussions concerning the format, tasks, and status of museum institutions in independent Poland, and also on their projects relating to establishing new museums. The analysis in this article is based on the opinions of Andrzej Niemojewski, Stanisław Sierosławski, Jadwiga Petrażycka-Tomicka, Maciej Szukiewicz, Stanisław Witkiewicz, and Stefan Żeromski. The considerations of Mieczysław Treter, as the director of the State Art Collections in Warsaw and author of the first Polish synthesis on Polish museums, are also examined in context. This article shows that museum projects proposed by Polish writers on the threshold of the Second Polish Republic became both a testimony of the reception of the entire 19th century museological tradition, and a sign of the awareness of the changes in thinking about the social role of museums, taking place from the first years of the 20th century and accelerated by the necessity of rebuilding the Polish state. It is also shown that the planning of museum transformations by Polish writers of the years 1914 to 1923 was done with reference to their thinking about literature and its reception, and thus, museum journalism became simultaneously a testimony of literary culture of that period.